2009
DOI: 10.1096/fasebj.23.1_supplement.599.4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in muscle carnosine of subjects with 4 weeks supplementation with a controlled release formulation of beta‐alanine (Carnosyn™), and for 6 weeks post

Abstract: Muscle Carnosine (M‐Carn) synthesis is limited by the availability of ?‐Alanine ( ?‐Ala) but can be increased by supplementation with ?‐Ala. This is of interest to athletes since increased levels of muscle M‐Carn have previously been shown to improve exercise performance. Above 10mg/kg bwt, however, ?‐Ala in solution or rapidly‐dissolving capsules causes symptoms of paraesthesia, despite the amount being less than that available from normal meat ingestion.PURPOSETo investigate the change in M‐Carn in subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
5
2
Order By: Relevance
“…Moreover, we used an 8-wk, high-dose, supplementation protocol, providing a total accumulated β-alanine dose of ~360 g, which resulted in ~90% increase in M-Carn. Both the total accumulated dose and the carnosine accrual in our study were substantially greater than the doses (~90 to 180 g) and the increases in M-Carn (<40% to 60%) shown in previous studies (17)(18)(19). This might account, at least in part, for some of the differences between our results and those previously reported (17)(18)(19).…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…Moreover, we used an 8-wk, high-dose, supplementation protocol, providing a total accumulated β-alanine dose of ~360 g, which resulted in ~90% increase in M-Carn. Both the total accumulated dose and the carnosine accrual in our study were substantially greater than the doses (~90 to 180 g) and the increases in M-Carn (<40% to 60%) shown in previous studies (17)(18)(19). This might account, at least in part, for some of the differences between our results and those previously reported (17)(18)(19).…”
Section: Discussioncontrasting
confidence: 84%
“…We also showed that carnosine washout can be described by a linear decay, although an exponential model can also describe the washout kinetics just as well as the linear model. The calculated t 1/2 for M-Carn was 4.6 (95% CI, 3.2-7.0) wk in the exponential decay model in our study, which is not too dissimilar to the 5.8 wk reported by Baguet et al (17) but somewhat shorter than the 8.6 wk reported by Harris et al (19). We also provided evidence for the association between M-Carn and high-intensity exercise performance after both supplementation and washout.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations